Assessing mechanical responses for damage detection in bridge spans through resonance region analysis - Quang Thanh, Nguyen; Ba Tu, Vu; Anh Tuan, Nguyen; Tien Thuy, Nguyen (Journal of Transportation Science and Technology, 2023)
This article introduces a new method for evaluating the mechanical behavior of structures to detect potential damages in bridge spans. The study enables us to monitor the stiffness degradation of bridge spans over time, operating under different working conditions. The proposed approach suggests monitoring the operational status of bridge spans at different measuring points, corresponding to different levels of applied load, measurement time, and environmental conditions according to the random theory. The study results demonstrate that changes in the area under the resonance regions of the power spectrum density can provide accurate information on the change in the structural behavior during operational periods. Furthermore, the research indicates that changes in the area under resonance regions can identify hazardous points on different spans of a bridge through different measuring points. Overall, in the future, this method can assist in identifying potential damages and warning of potential hazards to improve safety and reliability for people and vehicles crossing the bridge.